International and domestic legal frameworks on online fraud and deepfake technologies: a comparative criminal law analysis - Beaver, K.M. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The relevance of this study stems from the rapid development of digital technologies and the introduction of generative artificial intelligence, which has given rise to new forms of online fraud, particularly those involving deepfakes. These technologies, capable of producing audio and video content that is virtually indistinguishable from authentic sources, significantly enhance the manipulative potential of fraudulent schemes and complicate their detection. Existing international and national legal mechanisms remain insufficiently adapted to these emerging challenges. The article aims to provide a comparative analysis of international and domestic legal frameworks addressing online fraud involving deepfake technologies, to identify legal gaps, and to suggest directions for their resolution. The object of the research is deepfake technologies and social engineering in the context of fraud, while the subject concerns criminal law mechanisms for their prevention and prosecution. The methodological framework combines system and comparative analysis, content analysis of legal instruments and academic literature, case studies, as well as classification and generalization. The findings indicate that international instruments, such as the Budapest Convention, lack explicit provisions addressing deepfakes, thereby reducing legal certainty and requiring expansive interpretation. At the domestic level, substantial divergence is observed: while the United States, the United Kingdom, and the European Union are developing specialized norms, post-Soviet jurisdictions predominantly rely on general provisions on fraud and forgery. Judicial practice reveals difficulties in the qualification of offenses, detection of synthetic content, forensic examination, and ensuring consistency in enforcement. The study concludes that effective responses require the elaboration of specialized legal norms, the harmonization of international approaches, and the strengthening of institutional cooperation. The practical significance lies in providing recommendations for the modernization of national legal systems and the enhancement of international efforts to counter transnational threats of online fraud facilitated by deepfake technologies.